RÉVISION DE 1997 DES LOIS FÉDÉRALES SUR LES INSTITUTIONS FINANCIÈRES : vues de l’industrie canadienne des assurances de personnes - canadienne des compagnies d’assurance de personnes inc., Association (Assurances)

(untitled) (HEC Montréal, 1995)
According to the Canadian Life and Health Insurance Association Inc., the proposed legislative review in 1997 of the Canadian financial service industry must resolve some basic inequities between life and health insurers and banks. The last 1992 federal reform hurt competition by increasing concentration which goes against public interest, particularly the significant increase in ownership by some major banks. We are pleased to publish the CLHIA's submission addressed to the Minister of Finance, in June 1995, asking Ottawa to consider new rules that stimulate effective and fair competition between banks and the insurance sector.